Pollutant dispersion modelling (Dust, CO, NOx, and SOx) from palm oil mill stack (Case Study of PT. Mustika Agung Sawit Sejahtera) - Hermantika Sari, Nadya Hermantika x; Tarumun, Suardi; ', Saryono (Indonesian Journal of Environmental Science and Technology, 2014)
Pollutant dispersion  modeling study of a stack is one of the efforts in addressing  the problems  thatemissions of the palm oil industry can match the capacity of the environment, so it will not impact on the envi ronment  and society.  Screeen  view SCREEN3  software,  based of Gaussian  dispersion  method  for dust, CO, NOx, and SOx pollutant,  was used for pollutant  dispersiion modeling.  The input parameters  in the simulation were the rate of emission of pollutants  emitted from the stack, the air velocity around the source of emissions, atmospheric stability factor, and the topography of the site. While the expected output was a visualization of dis tribution of pollutants concentration  in the form of 2-dimensional  plane-shaped  contour that came with concen tration values of the distance from the source  of emission. Modeling  in this study was conducted  with several scenarios that the average meteorological  conditions at the time of measurement and the worst conditions. The results showed that the dominant wind direction was to the south with an average speed of 5.87 m/s. The result ing emission rate was 36.4 g/s. As for the pollutants, CO was 13.84 g/ s, SOx was 0.213 g/s and NOx 24.49 g/ s. Emission maximum distance was 1340 m from the stack with dust concentration  at 133.9 ug/m3   The concentra tions of CO, NOx, and SOx were 50.90 ug/m3   90.06 ug/m3;  0.7833 ug/m3  respectively.Keywords: environment,  pollutant  dispersion  modeling,  stack,  palm oil mill,  Gaussian  dispersion  method,  Screen  viewScreen3